TEACHER’S PROXIMITY IN CONDUCTING CLASSROOM MANAGEMENT (A Case Study on English Teachers of SMP Negeri 1 Lembang) - Dede Riska Ningrum (Journal of English and Education, 2017)
The aim of the study is to find out how teacher utilize Proximity in conducting classroom management. The research was held in a junior high school in Lembang. The participants of this study were two teachers of the school chosen, who are English teachers there. One teacher is female and another is male. Both teachers teach 8th grade. Three classes were chosen as the object of observation. This study was conducted using one of the Qualitative Research Design types, Case Study, as the research methodology. The data were obtained through classroom observation and interview. The result of this study shows that teachers utilized nonverbal communication in managing classroom. Among those nonverbal cues, teacher’s proximity was one of them. It was found that teachers should apply appropriate distance in certain situation. It was connected with the teachers’ characteristics, such as their mobility and understanding of students and the function of the distance. Several recommendations are offered for future researchers. It is expected the analysis to be more comprehensive because the limitation of participants. Last, it is recommended for future research, teacher’s proximity can be studied more deeply.